Cooperativismo de crédito: uma alternativa social e solidária nas relações financeiras - Rorato, Lucas Ferdinando [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The Social and Solidarity Economy (ESS) has been gaining great space in the academic environment, in public policies and in international debates in recent decades, due to its relevance in the face of socioeconomic problems that affect the most vulnerable layers of society. Among the countless organizations that make up the ESS framework, cooperativism is one of the strongest and most widespread movements in the world, in which it promotes the union of people who seek a common goal. According to Meinen & Port, (2012, p. 49) cooperativism is “a socioeconomic alternative based on values and principles, whose objective is to build a better life for millions of people around the world”. In Brazil, one of the strongest branches of cooperatives is credit, or finance, in which people come together to seek a fairer, more inclusive and democratic financial relationship. Thus, the objective of this work is to analyze and understand the characteristics and fundamentals of economics Social and Solidarity, analyzing the state of the art of credit unions, to investigate the hypothesis that this alternative model is a tool for financial inclusion. This investigation takes place through the analysis of the economic-financial performance of the largest credit union in Brazil, Sicoob Credicitrus.

A Economia Social e Solidária (ESS) vem ganhando grande espaço no ambiente acadêmico, nas políticas públicas e nos debates internacionais nas últimas décadas, em virtude de sua relevância frente à problemas socioeconômicos que atingem as camadas mais vulneráveis da sociedade. Dentre as inúmeras organizações que compõe o arcabouço da ESS, o cooperativismo é um dos movimentos mais fortes e difundidos pelo mundo, no qual promove a união de pessoas que buscam um objetivo em comum. Segundo Meinen & Port, (2012, p. 49) o cooperativismo é “uma alternativa socioeconômica baseada em valores e princípios, cujo objetivo é a construção de uma vida melhor para milhões de pessoas ao redor do mundo”. No Brasil, um dos ramos mais fortes do cooperativismo é o de crédito, ou financeiro, no qual pessoas se unem para buscar uma relação financeira mais justa, inclusiva e democrática. Desse modo, o objetivo do presente trabalho é analisar e compreender as características e fundamentos da Economia Social e Solidária, fazendo uma análise do estado da arte do cooperativismo de crédito, para investigar a hipótese desse modelo alternativo ser uma ferramenta de inclusão financeira. Essa investigação se dá por meio da análise do desempenho econômico-financeiro da maior cooperativa de crédito do Brasil, a Sicoob Credicitrus.
Financial cooperativism: a social and solidary alternative in financial relations
Keywords: Economia social e solidária; Cooperativismo de crédito; Relações financeiras